THE INFLUENCE OF WATCHING YOUTUBE PRONUNCIATION VIDEOS TOWARDS STUDENTS’ PRONUNCIATION ABILITY - Syaifudin Latif Darmawan (JL3T (Journal of Linguistics, Literature and Language Teaching))
In language teaching, media is one of the tools that very useful to support its successful teaching. In teaching pronunciation, the students need to give additional information how to pronounce words. One of the ways is by using Youtube pronunciation videos. By using Youtube pronunciation videos, the students will get more input and knowledge how to pronounce words from the native. The objective of this research is to know whether there is a significant influence of watching Youtube pronunciation videos towards students’ pronunciation ability. There were two variables in this research, the independent variable (X) was Youtube Pronunciation videos and dependent variable (Y) was the students’ pronunciation ability.